Teaching Hospital Financial Status and Patient Outcomes Following ACGME Duty Hour Reform. (2nd August 2012) - Navathe, Amol S.; Silber, Jeffrey H.; Small, Dylan S.; Rosen, Amy K.; Romano, Patrick S.; Even‐Shoshan, Orit; Wang, Yanli; Zhu, Jingsan; Halenar, Michael J.; Volpp, Kevin G.
Abstract : Objective: To examine whether hospital financial health was associated with differential changes in outcomes after implementation of 2003 ACGME duty hour regulations. Data Sources/Study Setting: Observational study of 3, 614, 174 Medicare patients admitted to 869 teaching hospitals from July 1, 2000 to June 30, 2005. Study Design: Interrupted time series analysis using logistic regression to adjust for patient comorbidities, secular trends, and hospital site. Outcomes included 30‐day mortality, AHRQ Patient Safety Indicators (PSIs), failure‐to‐rescue (FTR) rates, and prolonged length of stay (PLOS). Principal Findings: All eight analyses measuring the impact of duty hour reform on mortality by hospital financial health quartile, in postreform year 1 ("Post 1") or year 2 ("Post 2") versus the prereform period, were insignificant: Post 1 OR range 1.00–1.02 and Post 2 OR range 0.99–1.02. For PSIs, all six tests showed clinically insignificant effect sizes. The FTR rate analysis demonstrated nonsignificance in both postreform years (OR 1.00 for both). The PLOS outcomes varied significantly only for the combined surgical sample in Post 2, but this effect was very small, OR 1.03 (95% CI 1.02, 1.04). Conclusions: The impact of 2003 ACGME duty hour reform on patient outcomes did not differ by hospital financial health. This finding is somewhat reassuring, given additional financial pressure on teaching hospitals from 2011 duty hour regulations.